2011
DOI: 10.1289/ehp.1002169
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Organochlorine Compound Exposure, Rapid Weight Gain, and Overweight in Infancy

Abstract: BackgroundAlthough it has been hypothesized that fetal exposure to endocrine-disrupting chemicals may increase obesity risk, empirical data are limited, and it is uncertain how early in life any effects may begin.ObjectivesWe explored whether prenatal exposure to several organochlorine compounds (OCs) is associated with rapid growth in the first 6 months of life and body mass index (BMI) later in infancy.MethodsData come from the INMA (Infancia y Medio-Ambiente) Child and Environment birth cohort in Spain, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
133
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 74 publications
14
133
4
1
Order By: Relevance
“…Similar to previous studies conducted among subjects who experienced relatively high exposure, prenatal exposure to p,p´-DDE was not associated with BMI (Cupul-Uicab et al 2010;Gladen et al 2004) (see Supplemental Material, Table S7). Earlier studies that reported an association between DDE exposure and higher BMI during infancy and childhood (Mendez et al 2011;Valvi et al 2012;Verhulst et al 2009) had median levels of p,p´-DDE that were lower than or close to the lowest level of exposure found in the CPP participants (lowest value of p,p´-DDE in the CPP, 0.34 μg/g lipid). In addition, these non-null findings tended to be limited to certain subgroups (i.e., higher BMI with DDE exposure among children whose mothers smoked ever or among children whose mothers had a normal prepregnancy BMI) (Mendez et al 2011;Verhulst et al 2009).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similar to previous studies conducted among subjects who experienced relatively high exposure, prenatal exposure to p,p´-DDE was not associated with BMI (Cupul-Uicab et al 2010;Gladen et al 2004) (see Supplemental Material, Table S7). Earlier studies that reported an association between DDE exposure and higher BMI during infancy and childhood (Mendez et al 2011;Valvi et al 2012;Verhulst et al 2009) had median levels of p,p´-DDE that were lower than or close to the lowest level of exposure found in the CPP participants (lowest value of p,p´-DDE in the CPP, 0.34 μg/g lipid). In addition, these non-null findings tended to be limited to certain subgroups (i.e., higher BMI with DDE exposure among children whose mothers smoked ever or among children whose mothers had a normal prepregnancy BMI) (Mendez et al 2011;Verhulst et al 2009).…”
Section: Discussionmentioning
confidence: 81%
“…Earlier studies that reported an association between DDE exposure and higher BMI during infancy and childhood (Mendez et al 2011;Valvi et al 2012;Verhulst et al 2009) had median levels of p,p´-DDE that were lower than or close to the lowest level of exposure found in the CPP participants (lowest value of p,p´-DDE in the CPP, 0.34 μg/g lipid). In addition, these non-null findings tended to be limited to certain subgroups (i.e., higher BMI with DDE exposure among children whose mothers smoked ever or among children whose mothers had a normal prepregnancy BMI) (Mendez et al 2011;Verhulst et al 2009). In the present study, however, DDE did not µg/L CPP (1959-1965) NHANES (2003 show an interaction with maternal smoking or prepregnancy BMI.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…28 A recent study reported that maternal serum DDE levels were associated with rapid infant weight gain and elevated 14-month BMI in their offspring. 29 Certainly, more research in adults is needed from longitudinal studies of the effects of these chemicals on weight gain and on patterns of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging additional view hypothesizes that metabolic programming of obesity and metabolic risk may be linked to perinatal exposure to EDCs at low environmentally-relevant doses [94][95][96][97]. Indeed, it is well acknowledged that perinatal exposure to these compounds occurs with influence in birth weight and later health outcomes [98][99][100][101][102][103].…”
Section: Endocrine Disruptors and In Utero Effectsmentioning
confidence: 99%